Microsoft Azure Administrator Associate (AZ-104) Cert Prep by Microsoft Press. - Hargreaves, Brett; Press, Microsoft (linkedin.com, 2024)
This course is designed to prepare learners for the Microsoft Azure Administrator Associate (AZ-104) exam.